Coking pressure and coke structure - Eleni Psomiadou (1993)
The carbonization of some low volatile matter coals for the production of metallurgical coke in slot type ovens is accompanied by the exertion of pressures on the walls which can be dangerous and destroy the walls. It is generally accepted that coking pressure originates from the volatile matter released from the coal being retained as pressurized vapours trapped within the plastic layer of the carbonizing coal charge. Pressure during carbonization also influences the nature of the carbon texture and the porous structure of coke is strongly dependent on volatile matter release during the plastic stage of the carbonization process. There is therefore a possible association of coking pressure, coke porous structure and coke carbon texture. Seven coals giving a variety of wall pressures, as measured in a movable-wall oven,ranging from safe to dangerously coking, were carbonized in a small laboratory oven. The textural compositions of the resultant cokes were assessed by polarized light microscopy while pore structural parameters were measured by computerized image analysis.The textural compositions varied with volatile matter content of the coals while the porosities varied linearly with the internal gas pressures measured in a single plastic layer. In an attempt to investigate possible relations between the pore structure development and internal gas pressures generated in a single plastic layer, polished surfaces showing the coal-to-coke transformation were prepared after quenching carbonized single-wall oven charges. These surfaces were studied by image analysis techniques to obtain measurements of the pore sizes as carbonization proceeded. Pore sizes generally rose to a maximum within the plastic temperature range before falling to the almost constant value seen in the semicoke. No systematic variation between the pore structure development and the internal gas pressures could be established.